Estudio dasométrico de la especie Cedrelinga cateniformis Ducke (tornillo) del bosque tropical de Puerto Almendra, San Juan, Maynas, Loreto, 2023 - Haro Piña, Diego Rafael (2024)
The present study was carried out in the facilities of the tropical forest of Puerto Almendra, district of San Juan, Maynas, with the purpose of knowing the behaviour of the anual volumetric increase of the species Cedrelinga cateniformis Ducke (torni lo) of the tropical foresto f Puerto Almendra. From the obtained results, it was determined through the stem and leaf diagram that the greatest abundance of tree diameters is found in stem 6, which has 6 trees of 65 cm, 1 of 66cm, 4 of 67 cm and 4 of 68 cm, which add up to a total of 29 trees. The uotliers of the set of inventoried tres are base tres 3 and 10 with 4 and 1 tree respectively. Adding up only 4.67% of the total. The largest diameters are found between the stems 8.9 10 with 16 units. The fashion is locate don stem 6 with 10 units and 5 leaves each, (65 cm). The standard deviation 16, coefficient of variation 26, range 69, arihmetic mean 62 cm (0.62 m), root mean square 62 cm, median is 54 cm. The periodic growth (ICA) is 189cm/year and the average anual growth (IMA) is 189cm/year.